2023
DOI: 10.1007/s11831-023-09913-0
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Conditioning of Immersed Finite Element Methods: Analysis and Remedies

Abstract: This review paper discusses the developments in immersed or unfitted finite element methods over the past decade. The main focus is the analysis and the treatment of the adverse effects of small cut elements. We distinguish between adverse effects regarding the stability and adverse effects regarding the conditioning of the system, and we present an overview of the developed remedies. In particular, we provide a detailed explanation of Schwarz preconditioning, element aggregation, and the ghost penalty formula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 239 publications
0
2
0
Order By: Relevance
“…In ghost penalty formulations, one can readily use the non-aggregated spaces on the active mesh and add stabilization terms (see, e.g., [33]) to make the problem robust with respect to cut locations. Thus, the space-time FE spaces to be used in this case is simply V 𝑛 ℎ .…”
Section: Space Time Unfitted Finite Element Methodsmentioning
confidence: 99%
“…In ghost penalty formulations, one can readily use the non-aggregated spaces on the active mesh and add stabilization terms (see, e.g., [33]) to make the problem robust with respect to cut locations. Thus, the space-time FE spaces to be used in this case is simply V 𝑛 ℎ .…”
Section: Space Time Unfitted Finite Element Methodsmentioning
confidence: 99%
“…u(x, y, 0) = 1 Ω (x, y)u 0 (x, y), (x, y) ∈ Ω, u(x, y, t) = 0, (x, y) ∈ R 2 ⧵ Ω and t ∈ (0, T], (17) then the computation of the symbol can still be performed by resorting to the GLT theory. Indeed, the discretization of Equation ( 17) in matrix form reads as (10) and (11), and it can be easily shown that…”
mentioning
confidence: 99%
“…In ghost penalty formulations, one can readily use the non-aggregated spaces on the active mesh and add stabilization terms (see, e.g., [42]) to make the problem robust with respect to cut locations. Thus, the space-time FE spaces to be used in this case is simply V n h .…”
Section: Space-time Finite Element Spacesmentioning
confidence: 99%